PENGEMBANGAN MEDIA PEMBELAJARA PAPAN PINTAR PADA KETERAMPILAN MEMBACA PERMULAAN PESERTA DIDIK KELAS II - Wiguna Rosianti; M. Anggrayni; Martiya Nurni Khairita (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
Wiguna Rosianti, 2025. Development of Smart Board Learning Media for Early Reading Skills of Second Grade Students. Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Dharmas Indonesia. This study aims to develop a smart board learning media that is valid, practical, and effective in improving the early reading skills of second grade students at SDN 13 Koto Baru. The background of this research stems from the low early reading ability of students, which is caused by the use of monotonous lecture methods and the lack of engaging learning media. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The product developed is a smart board made from plywood measuring 40 x 25 cm, featuring images and letters that can be arranged by students. The validity of the media was assessed by content, language, and media experts; its practicality was evaluated based on responses from teachers and students; and its effectiveness was measured through students' learning outcomes. The results show that the developed smart board media is highly valid, practical to use in the learning process, and effective in improving students’ early reading skills. This research concludes that smart board media can serve as an alternative solution in teaching Indonesian language at the elementary level, particularly in the domain of early reading.